Solusi Al-Qur’an Terhadap Matinya Kepakaran: (Telaah Penafsiran QS. Al-Syūrā [42] Ayat 3 Dan QS. Al-Baqaraħ [2] Ayat 233 - Abd Muid Nawawi; Saifuddin Zuhri; Muhammad Aqil Rabbani (Pusat Penelitian dan Pengabdian Masyarakat (P3M) Sekolah Tinggi Ilmu Al-Qur'an (STIQ) ZAD Cianjur, 2022)
This phenomenon of the Death of Expertise is a consequence of an era of disruption that results in attacks on established knowledge. This research tries to find a solution to the phenomenon of the death of expertise by conducting a study of the interpretation of interpreters on verses relevant to this phenomenon. This research includes qualitative research where data collection is carried out using the library research method. In addition, the author uses the maudhû'i (thematic) interpretation method where the author collects verses of the Qur'an from various surahs related to the problem of the death of expertise, then examines various interpretive literature related to these verses so that a series of solutions are found that are assumed to be able to overcome the phenomenon of the death of expertise. The author finds that improving the quality of deliberation is one of the solutions to the death of expertise, where the death of expertise is caused by the poor quality of communication of experts-ordinary people. Therefore, quality deliberation must become the culture of the community in communicating. So that communication between experts and ordinary people can be re-directed.